2010
DOI: 10.1016/j.jsb.2010.03.019
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between apo and complexed structures of bothropstoxin-I reveals the role of Lys122 and Ca2+-binding loop region for the catalytically inactive Lys49-PLA2s

Abstract: Phospholipases A(2) (Asp49-PLA(2)s) are enzymes responsible for cellular membrane disruption through Ca(2+)-dependent hydrolysis of phospholipids. A class of these proteins (Lys49-PLA(2)s) does not show catalytic activity but can exert a pronounced local myotoxic effect that is not neutralized by serum therapy. In this work, we present five structures of Lys49-PLA(2)s from snakes of the Bothrops genus in apo form, complexed with PEG molecules and chemically modified by p-bromofenacil bromide (BPB), a classic i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
54
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(59 citation statements)
references
References 48 publications
4
54
0
1
Order By: Relevance
“…Such changes have been shown by crystallography in the bovine pancreatic PLA 2 (Renetseder et al, 1988) and the non-myotoxic, acidic PLA 2 BthA-I from Bothrops jararacussu venom (Magro et al, 2005), although not in the case of the acidic APLA 2 from Agkistrodon halys venom (Zhao et al, 1998). Moreover, conformational changes induced by p -BPB have also been demonstrated for two Lys49 myotoxins, PrTX-I from B. pirajai (Marchi-Salvador et al, 2009) and BthTX-I from B. jararacussu (Fernandes et al, 2010). These myotoxins, in spite of being enzymatically inactive, suffer a reduction in myotoxicity of nearly 50% when modified by p -BPB, which has been possibly attributed to the conformational changes caused by the alkylation of their absolutely conserved His48 (Díaz et al, 1993; Andrião-Escarso et al, 2000; Soares et al, 2000; Marchi-Salvador et al, 2009).…”
Section: Resultsmentioning
confidence: 90%
“…Such changes have been shown by crystallography in the bovine pancreatic PLA 2 (Renetseder et al, 1988) and the non-myotoxic, acidic PLA 2 BthA-I from Bothrops jararacussu venom (Magro et al, 2005), although not in the case of the acidic APLA 2 from Agkistrodon halys venom (Zhao et al, 1998). Moreover, conformational changes induced by p -BPB have also been demonstrated for two Lys49 myotoxins, PrTX-I from B. pirajai (Marchi-Salvador et al, 2009) and BthTX-I from B. jararacussu (Fernandes et al, 2010). These myotoxins, in spite of being enzymatically inactive, suffer a reduction in myotoxicity of nearly 50% when modified by p -BPB, which has been possibly attributed to the conformational changes caused by the alkylation of their absolutely conserved His48 (Díaz et al, 1993; Andrião-Escarso et al, 2000; Soares et al, 2000; Marchi-Salvador et al, 2009).…”
Section: Resultsmentioning
confidence: 90%
“…One of the main components of bothropic and other snake venoms are the phospholipases A 2 , enzymes which are able to promote Ca 2+ -dependent hydrolysis of sn- 2 acyl groups of membrane phospholipids, releasing free fatty acids and lysophospholipids [8]. A subgroup of these proteins, the Lys49-phospholipases A 2 (PLA 2 s), are catalytically inactive due to the lack of Ca 2+ coordination related to the natural mutations Tyr28→Asn and Asp49→Lys [9], [10], but, in association with metalloproteases, may cause permanent tissue loss, disability and even require limb amputation due to local myonecrosis inefficiently neutralized by serum therapy [5].…”
Section: Introductionmentioning
confidence: 99%
“…Experiments based on electrophoresis, spectroscopy [11], [12], crystallography [13], [14], [15], [16] small angle X-ray scattering [17] and dynamic light scattering [10] have brought important insights into the structural features of these molecules demonstrating that the bothropic Lys49-PLA 2 s are dimeric in solution. Crystallographic studies also revealed that these proteins have a dimeric structure and a biological unit held by contacts between the tips of β-wing segments and N-terminal α-helices from both monomers [13].…”
Section: Introductionmentioning
confidence: 99%
“…The buried surface area 312 was found to be 362.9 Å 2 . type II PLA2 [18][19][20][21][22][23][24][25]. In the other two cases, the compounds (iv) and 347 (v) were not able to slide deeply enough into the cleft due to steric con- Ser70 and Arg72 (Fig.…”
Section: Ligand Concentration In μMmentioning
confidence: 99%
“…This 56 common moiety may be designed and optimized for achieving optimal 57 binding potential to both enzymes, PLA2 and COX-2. So far, a number of 58 structures of the complexes of type II PLA2 with various compounds 59 are available [18][19][20][21][22][23][24][25][26][27][28][29][30]. Yet more insights into the mode of binding guity.…”
mentioning
confidence: 99%